Attenuation of near-IR light through dentin at wavelengths from 1300–1650-nm - Chan, Andrew C. (2014)
Light scattering in dental enamel decreases markedly from the UV to the near-IR and recent studies employing near-IR transillumination and reflectance imaging including optical coherence tomography indicate that this wavelength region is ideally suited for imaging dental caries due to the high transparency of enamel. The opacity of dentin is an important factor in optimizing the contrast of demineralization in reflectance measurements. It also influences the contrast of occlusal lesions in transillumination. Light scattering in dentin is an order of magnitude larger than in enamel, it is highly anisotropic and has a different spectral light scattering dependence than enamel. The objective of this study was to measure the optical attenuation of near-IR light through dentin at near-IR wavelengths from 1300–1650-nm. In this study the collimated transmission of near-IR light through polished thin sections of dentin of 0.05 to 0.6 mm thickness was measured. Beer-Lambert plots show that the attenuation coefficients range in magnitude from 20 to 40 cm(−1). Attenuation increased significantly with increasing wavelength and the increases were not entirely consistent with increased water absorption.